3-D interactive visualisation tools for Hi spectral line imaging. Issue Volume 12:Issue S325(2016) (30th May 2017) - van der Hulst, J. M.; Punzo, D.; Roerdink, J. B. T. M.
Abstract: Upcoming HI surveys will deliver such large datasets that automated processing using the full 3-D information to find and characterize HI objects is unavoidable. Full 3-D visualization is an essential tool for enabling qualitative and quantitative inspection and analysis of the 3-D data, which is often complex in nature. Here we presentSlicerAstro, an open-source extension of3DSlicer, a multi-platform open source software package for visualization and medical image processing, which we developed for the inspection and analysis of HI spectral line data. We describe its initial capabilities, including 3-D filtering, 3-D selection and comparative modelling.